2007
DOI: 10.1080/17439760701228920
|View full text |Cite
|
Sign up to set email alerts
|

Purpose in life and reasons for living as mediators of the relationship between stress, coping, and suicidal behavior

Abstract: Positive psychological factors that help protect vulnerable persons from suicidal behavior are vital in understanding resiliency and suicide prevention. The purpose of the current study was to examine whether positive factors (including purpose in life, reasons for living, and coping styles) mediate the relationship between stressful life events and suicidal behaviors among 416 college student volunteers. Reasons for living inversely predicted suicidal behavior and thoughts directly as well as indirectly via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 31 publications
4
63
1
9
Order By: Relevance
“…For example, in a study investigating the variety of needs that humans aim to fulfill in order to consider their lives meaningful, Crescioni and Baumeister (2013) reported that "when individuals talk of finding meaning in their lives … they seek to interpret their own actions and experiences in terms of an existentially meaningful life story," with "such stories depict [ing] actions and decisions as following from important, stable values and contributing to the fulfillment of one or more crucial goals" (p. 3). In another study investigating whether positive factors (including purpose in life, reasons for living, and coping styles) mediated the relationship between stressful life events and suicidal behaviors among participants (n = 416) in college, Wang, Lightsey, Pietruszka, Uruk, and Wells (2007) reported that "both purpose in life and reasons for living had inverse effects on depression, the higher the purpose in life and reasons for living, the lower the depression, and the lower the relationship between depression and suicidal ideation/behavior," and that accordingly, "purpose in life and reasons for living were found to be important predictors of suicide and may reduce the likelihood of suicidal thoughts and behaviors" (p. 202). Moreover, in other recently published work, Bronk, Hill, Lapsley, Talib, and Finch (2009) investigated the relationship among purpose, hope, and life satisfaction among participants (n = 806) and found that "having identified a purpose in life is associated with greater life satisfaction in adolescence, emerging adulthood, and adulthood" (p. 506), Chamberlain and Zika (1992) investigated religiosity as a predictor of meaning in life in a sample of participants (n = 188) and found that "the relationship between life satisfaction and religiosity may well be mediated by meaningfulness" (p. 415), and Byron and Miller-Perrin (2009) investigated the relationship between faith, life purpose, and wellbeing in participants (n = 103) and found that "faith and life purpose contribute to the development of well-being and may be important characteristics to foster in order to enhance one's personal sense of well-being," and that their "results indicated that life purpose completely mediated the relationship between faith and well-being," which suggests that "the impact of faith on well-being can be explained by life purpose" (p. 68).…”
Section: Flourishing With Music and Meaningmentioning
confidence: 99%
“…For example, in a study investigating the variety of needs that humans aim to fulfill in order to consider their lives meaningful, Crescioni and Baumeister (2013) reported that "when individuals talk of finding meaning in their lives … they seek to interpret their own actions and experiences in terms of an existentially meaningful life story," with "such stories depict [ing] actions and decisions as following from important, stable values and contributing to the fulfillment of one or more crucial goals" (p. 3). In another study investigating whether positive factors (including purpose in life, reasons for living, and coping styles) mediated the relationship between stressful life events and suicidal behaviors among participants (n = 416) in college, Wang, Lightsey, Pietruszka, Uruk, and Wells (2007) reported that "both purpose in life and reasons for living had inverse effects on depression, the higher the purpose in life and reasons for living, the lower the depression, and the lower the relationship between depression and suicidal ideation/behavior," and that accordingly, "purpose in life and reasons for living were found to be important predictors of suicide and may reduce the likelihood of suicidal thoughts and behaviors" (p. 202). Moreover, in other recently published work, Bronk, Hill, Lapsley, Talib, and Finch (2009) investigated the relationship among purpose, hope, and life satisfaction among participants (n = 806) and found that "having identified a purpose in life is associated with greater life satisfaction in adolescence, emerging adulthood, and adulthood" (p. 506), Chamberlain and Zika (1992) investigated religiosity as a predictor of meaning in life in a sample of participants (n = 188) and found that "the relationship between life satisfaction and religiosity may well be mediated by meaningfulness" (p. 415), and Byron and Miller-Perrin (2009) investigated the relationship between faith, life purpose, and wellbeing in participants (n = 103) and found that "faith and life purpose contribute to the development of well-being and may be important characteristics to foster in order to enhance one's personal sense of well-being," and that their "results indicated that life purpose completely mediated the relationship between faith and well-being," which suggests that "the impact of faith on well-being can be explained by life purpose" (p. 68).…”
Section: Flourishing With Music and Meaningmentioning
confidence: 99%
“…More recently, this perspective continues with studies that link lower levels of purpose in life with living with HIV disease (Lyon & Younger, 2001), higher levels of suicidal ideation (Edwards & Holden, 2001), higher levels of general anxiety (Bigler, Neimeyer, & Brown, 2001), higher levels of fear of death and death avoidance (Ardelt, 2003(Ardelt, , 2008, higher levels of depression (Heisel & Flett, 2004;Hedberg, Gustafson, Aléx, & Brulin, 2010), higher risk of suicidal behaviours (Wang, Lightsey, Pietruszka, Uruk, & Wells, 2007), higher risk of psychosis and psychotic episodes (Turner, Jackson, Renwick, Sutton, & Foley, 2007), and higher risk of addiction to substances (Martin, MacKinnon, Johnson, & Rohsenow, 2011).…”
Section: Purpose In Life and Psychological Enquirymentioning
confidence: 99%
“…Having reasons for living (i.e., adaptive reasons that support not committing suicide) was protective against female suicidal thoughts and behaviors suicidal ideation and attempt adolescents from various socioeconomic backgrounds and suicidal ideation among urban African American youth [59][60][61]24]. Wang and colleagues found that purpose in life protected a sample of predominantly European and African American adolescents (ethnic differences were not indicated in the results) from suicidal ideation and attempts via an inverse relationship with depression [59]. Lastly, life satisfaction protected male African American adolescents from suicidal ideation and attempts [60].…”
Section: Personal Factorsmentioning
confidence: 99%
“…Fourteen studies reported on the effectiveness of personal factors as being protective against suicidality [2,3,12,15,16,23,24,28,40,46,48,[59][60][61]. Personal factors identified as protective against African American adolescent suicidality were age, self-esteem, emotional well-being, academic achievement/grade point average, hope, ascribing to an adaptive attributional style, avoidance-oriented coping, negative attitude toward suicide acceptability, reasons for living, purpose in life, and life satisfaction.…”
Section: Personal Factorsmentioning
confidence: 99%
See 1 more Smart Citation